Macroeconomic Volatility and Welfare in Developing Countries - Loayza, Norman V.; Rancière, Romain; Servén, Luis; Ventura, Jaume (World Bank, 2012)
Macroeconomic Volatility and Welfare in Developing Countries: An Introduction Norman V. Loayza, Romain Ranciere, Luis Serven, ` and Jaume Ventura Macroeconomic volatility, both a source and a reflection of underdevelopment, is a fundamental concern for developing countries. This article provides a brief overview of the recent literature on macroeconomic volatility in developing countries, highlighting its causes, consequences, and possible remedies. to reduce domestic policy-induced macroeconomic volatility by controlling the level and variability of fiscal expenditures, by keeping inflation low and stable, and by avoiding price rigidity (including that of the exchange rate), which eventually leads to drastic adjustments. The ability to conduct countercyclical fiscal policies is crucial, and it depends largely on the ability of the authorities to reduce public indebtedness to internationally acceptable levels, establish a record of saving in good times to provide for bad times, and develop credibility that forestalls perceptions of wasteful spending and default risk. Governments can reduce financial fragilities and deepen financial markets by eliminating implicit insurance schemes (such as fixed exchange rate regimes) and credit restrictions that distort the valuation of financial assets and liabilities. Following Ehrlich Becker's (1972) classic "comprehensive insurance" framework, three possible options can be identified: Self-protection (reducing the exposure to risk through, for instance, limited trade and financial openness). Primiceri and van Rens (2006*) explore the source of this increase by examining the consumption behavior of a large panel of individuals, finding that their behavior is consistent with an increase in the persistence of individual income shocks. Loayza and Raddatz (2007*) analyze how financial openness and trade openness, as well as product-market flexibility, factor-market flexibility, and domestic financial development, influence the impact of terms of trade shocks on output. To obtain their measure of policy volatility, the authors construct a measure of exogenous policy decisions unrelated to the state of the economy and take the standard deviation of this measure as a proxy for policy volatility. Even so, the literature and the lessons from the Barcelona conference reviewed here can provide some elements of sensible policy recommendations and identify areas where research is especially needed.